PENGARUH KEDISIPLINAN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA LEMBAGA AMIL ZAKAT NASIONAL (LAZNAS) DOMPET PEDULI UMMAT DAARUT TAUHIID CABANG BANDAR LAMPUNG - Alfian, Firmansyah Yunialfi; Anand, M Zulfy (Jurnal Manajemen Magister Darmajaya, 2018)
Performance problem which happened at Lembaga Amil Zakat Nasional (LAZNAS) Dompet Peduli  Ummat  Daarul  Tauhid  Bandar  Lampung  branch  was  the  employee performance result was not relevant with what the zakat recipient institution expected. The study aim was to analyze the effect of Work Discipline and Work Commitment on Employee Performance at Lembaga Amil Zakat Nasional Dompet Peduli Ummat Daarul Tauhiid Bandar Lampung branch. The type of this study used quantitative with an associative method through cause effect method. The sample collecting method used saturated sampling technique. The data collecting method used questionnaire and interview. The data analysis used double linear regression through t test and F test. The population was all employees of Lembaga Amil Zakat Nasional (LAZNAS) Dompet Peduli Ummat Daarut Tauhiit Bandar Lampung branch as 42 people. The research result shows that Work Discipline and Work Commitment significantly affected Employee Performance at Lembaga Amil Zakat Nasional (LAZNAS) Dompet Peduli Ummat Daarut Tauhiid Bandar Lampung branch simultaneously and partially.Keywords — Work Discipline, Work Commitment and Performance